Outdoor Study as a Contextual Learning Method in Geography - Noi, Siskawati; Lukum, Astin (EDUCTUM: Journal Research, 2025)
This study aims to 1) Analyze the application of outdoor study in Geography learning at the high school level, 2) Identify materials that are often taught using the outdoor study method, 3) evaluate the effectiveness of outdoor study in improving students’ understanding of geographical concepts contextually. This study uses a systematic review method by identifying, evaluating, and interpreting all relevant research results related to the research objectives. The results show that outdoor study is effective in improving students’ motivation and learning outcomes. Materials that are often delivered through outdoor study include the environment and sustainable development, which are reflected in direct observation of natural and social phenomena. The outdoor study method can effectively improve students’ understanding of geographical concepts contextually. This study concludes that the Application of Outdoor Study can be effectively applied in Geography learning at the high school level by providing direct learning experiences that are relevant to the material. Geography materials that are often taught using the outdoor study method are topics related to the environment and sustainable development. The effectiveness of Outdoor Study has been proven to improve students’ understanding of geographical concepts contextually, as well as foster social skills and concern for the surrounding environment.